Neo management and intelligent business ecosystems - Soto Ortigoza, Maricarmen; Prato Zuluaga, Rubén (REVISTA CIENTIFICA GLOBAL NEGOTIUM, 2024)
A modern approach to business organization puts into focus the new approach of the business ecosystem for the demands of the global environment. In this regard, the quest is centered on optimizing networks, suppliers, distributors, customers, competitors, and government agencies involved in delivering a specific product or service through competition and collaboration. Furthermore, it emphasizes intelligent data, with advanced systems to optimize efficiency, decision-making, and real-time interconnection, leading to a more effective and adaptive operation in Neo-management. But are organizations in Latin America prepared for this in terms of training profile and infrastructure? Therefore, the general objective was to analyze Neo-Management and intelligent business ecosystems. Framed in a paradigmatic complementarity, the research type was descriptive, documentary-bibliographical with a mixed approach by using quantitative data and phenomenological-hermeneutic methods. Among the relevant results obtained, the trend is that transformation and the way businesses are conducted are sought by a few to achieve more competitive and sustainable results. It is concluded that companies must reorganize with this neo-managerial philosophy towards achieving organizational networks or alliances, collaborative and competitive scenarios, creating advantages and greater value, as well as promoting the importance nowadays of intelligent business ecosystems based on innovation, entrepreneurial strategies, and transfers for competitiveness.